Pembiayaan Swadaya dan Kepemimpinan Informal dalam Pemberdayaan Masyarakat Desa Wisata Bukit Tawap, Kabupaten Sumenep - Widyawati Widyawati; Rohim Rohim (Jurnal Multidisiplin Indonesia, 2026)
This study examines community empowerment in a tourism village built entirely through community self-financing without any external support. Using a qualitative descriptive case-study approach in Pagarbatu Village, Saronggi Sub-district, Sumenep Regency, data were collected through in-depth interviews, participant observation, and documentation, and analysed with the interactive model of Miles and Huberman within the Asset-Based Community Development (ABCD) framework. The findings reveal that the Tabungan Warga Pagarbatu (TAWAP) collective savings system functions as an effective trust-based financing instrument that replaces formal funding from government or investors. Informal leadership exercised by the village head served as the catalyst that mobilised participation, transformed the tradition of gotong royong into a productive economic instrument, and sustained an implicit social contract among residents. Supporting factors include high social capital, value-based leadership, and digitally literate youth, while inhibiting factors include limited digital infrastructure, restricted budgets, and weak institutionalisation. The study proposes a replicable, self-reliant empowerment model that integrates communal savings, informal leadership, gender inclusion, and youth-led digital marketing.